Exclusionary Rule As The Defendant's Rights In Criminal Jurisdiction - Rizka Fakhry Alfiananda,; Sondakh, Devy K. G; Pinasang, Ralfie (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
The exclusionary rule is basically one of the principles that developed along with the development of criminal evidence law, especially in countries with anglo-Saxon legal traditions. The principle that emphasizes the exclusion or exclusion of evidence obtained unlawfully in the criminal justice process has over time become a procedural element that supports the creation of a fair trial for the Defendant. The right to a fair trial is a right that must be guaranteed by the State and does not only concern the right to be tried by an independent and impartial court. Indonesia as a state of law that tries to balance the public interest in law enforcement with the interests of the suspect or defendant in a fair judicial process unfortunately has not regulated exclusionary rule in its criminal procedural law. In fact exclusionary rule is one of the instruments for recovery in the event of a violation by law enforcement officials, especially in the process of obtaining evidence. Through research conducted using this normative legal research method, the author wants to place the exclusionary rule not only as a principle but also as a defendant's right in the criminal justice process as an inseparable part of the right to a fair trial so that it is urgent to be accommodated in the agenda of procedural law reform. Indonesian crime.